Poor awareness of syphilis prevention and treatment knowledge among six different populations in south China - Xiaobing Wu; Fuchang Hong; Lina Lan; Chunlai Zhang; Tiejian Feng; Yingzhou Yang (BMC, 2016)
Abstract Background China is facing an emerging epidemic of syphilis, and the cities in south China are most affected. Knowledge is a key factor in the prevention of syphilis infection, however, little is reported about how much people know about syphilis. This study was aimed at assessing peoples' awareness status in a city located in south China. Methods Six populations were recruited for this study, including urban residents, factory workers, college students, pregnant women, female sex workers (FSWs), and men who have sex with men (MSM). A questionnaire designed by the National Center for Disease Control and Prevention was used to assess participants' awareness of syphilis knowledge. About 5 % of participants were randomly selected to conduct a telephone survey for confirming the validity of fieldwork. Results The study recruited 3470 participants, and 61.2 % of participants were assigned to the awareness group. College students had the smallest percentage of awareness at 51.7 % (371/718), followed by FSWs at 53.9 % (200/371), factory workers at 56.0 % (381/679), urban residents at 65.4 % (435/665), pregnant women at 66.0 % (451/683), and MSM at 81.1 % (287/354). Multivariate logistic regression analysis showed that MSM and FSWs-but not factory workers and pregnant women-had more awareness of syphilis knowledge when comparing with urban residents; however, college students presented less awareness of syphilis knowledge than urban residents. Participants of younger age, of female gender, with lower education levels and without Shenzhen hukou possessed less awareness of syphilis knowledge than those of older age, of male gender, with higher education levels and with Shenzhen hukou respectively. Conclusions The percentages of awareness on syphilis knowledge found in this study are far from the benchmark set in the national 10-year plan. Tailored interventions for different subgroups to increase syphilis awareness are urgently warranted.